(untitled) (Human Factors in Design, 2022)
The objective was to review the use of Lean in Brazilian health services, with a focus on improving communication. A systematic review of articles in Portuguese and English was carried out in Science Direct, Embase, Scopus, PubMed and WebofScience databases. Among the 294 articles found, 18 were selected. The implementation of Lean philosophy is centered on surgical services in hospitals in the Southeast of Brazil. The main communication barriers identified were the flow of information, and communication between teams from different health sectors. The tools with the greatest applicability to identify and solve communication barriers were Value Stream Mapping, Visual Management, Gemba Walk, Poka Yoke, Kanban and Kaizen.